Community Response to Village Information System (SID) in Basic Services In East Lombok Regency - Dian Lestari Miharja; Agus Purbathin Hadi; Diyah Indiyati; Eka Putri Paramitha (Universitas Mataram, 2021)
This study aims to determine the public's response to use SID as a medium for basic social services, SID as a source of information, and SID as a community medium. This research can provide information about the readiness of the community to face the 4.0 revolution era, especially people in rural areas. If the community is ready and accustomed to using SID as a basic social service center and the other hand, managing resources continue to increase their capacity both in human resources and infrastructure, then SID can become a reliable database and can provide basic social services one-stop service in the village. This study used a qualitative descriptive method, data collecting on informants was carried out using in-depth interviews, direct observation, sampling techniques, documentation, and FGD. Then simultaneously carried out data analysis with interactive analysis methods. Key informants were the Village Head and SID Managers in Rarang Selatan and Kalijaga Timur Villages; as well as informants from village residents as many as 50 informants each 25 informants per village (consisting of elements of teachers, students, agricultural extension workers, heads of farmer groups, farmers, heads of farmer groups, Posyandu cadres, hamlet heads, housewives, traders). The results showed that the public response to SID as a service medium was positive, as a source of information was positive, and as a community medium was positive. This is shown by the behavior of the community using SID intensively, participating in disseminating the existence of SID, inviting villagers to take advantage of SID, even taking part in providing information (filling in content) to be conveyed to the community (especially village communities) through SID.Keywords: Response, Village Information System (SID), resources, community media, basic social services